Compensatory mechanisms in γδ T cell-deficient chickens following Salmonella infection - Tetzlaff, Felix; Methner, Ulrich; von Heyl, Theresa; Menge, Christian; Schusser, Benjamin; Berndt, Angela (Frontiers in Immunology, 2025)
Avian γδ T lymphocytes are highly abundant in the intestinal mucosa and play a critical role in immune defense against infectious diseases in chickens. However, their specific contributions to infection control remain poorly understood. To investigate the role of γδ T cells and their possible compensation, we studied wild-type and γδ T cell knockout chickens following infection with Salmonella Enteritidis. Bacterial loads in the liver, cecal content, and cecal wall were quantified. Immune cell populations in blood, spleen, and cecum were analyzed using flow cytometry. Immune gene transcription in sorted γδ (TCR1+) and TCR1- cell subsets as well as cecal tissue was measured by RT-qPCR. Strikingly, chickens lacking γδ T cells had significantly higher bacterial loads in the liver and more extensive Salmonella invasion in the cecal wall during the early stages of infection compared to wild-type birds. In blood, infected γδ T cell knockout chickens displayed a significantly increased percentage of CD25+ NK-like cells. In both blood and tissue, infected wild-type chickens demonstrated an increased absolute number of CD8αα+hi γδ T cells (CD4-). Conversely, γδ T cell knockout chickens exhibited an augmented cell count of a CD8αα+hiCD4-TCR1- cell population after infection, which might include αβ T cells. At 7 days post infection (dpi), gene expression analysis revealed elevated transcription of the activation marker IL-2Rα and proinflammatory cytokines (IL-17A, IFN-γ) in CD8αα+hiCD4-TCR1- cells from γδ T cell knockout chickens compared to CD8αα+hi γδ T cells from wild-type birds. By 12 dpi, these differences diminished as transcription levels increased in γδ T cells of wild-type animals. Our findings demonstrate that γδ T cells play a role in early immune protection against Salmonella Enteritidis infection in chickens. In later stages of the infection, the γδ T cells and their functions appear to be replaced by other cells.